2023
DOI: 10.1093/ehjopen/oead039
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage strain predicts subclinical atrial fibrillation in embolic strokes of undetermined source

Abstract: Aims Left atrial (LA) strain is promising in prediction of clinical atrial fibrillation (AF) in stroke patients. However, prediction of subclinical AF is critical in patients with embolic strokes of undetermined source (ESUS). The aim of this prospective study was to investigate novel LA and left atrial appendage (LAA) strain markers in prediction of subclinical AF in ESUS patients. Methods and results A total of 185 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A recent prospective observational study found that the global longitudinal strain (GLS) was lower in patients with acute embolism (p < 0.001) and allowed for the identification of patients with acute embolism (p < 0.0001) when compared to controls [94]. Other studies have similarly found that LAA strain has a similar predictive power for ischaemic stroke compared to the CHADS-VASC2 score [95,96], and others' findings show that LAA strain can predict subclinical AF for patients with cryptogenic stroke [97]. GLS may also be able to predict post-stroke mortality [94].…”
Section: Ttementioning
confidence: 89%
“…A recent prospective observational study found that the global longitudinal strain (GLS) was lower in patients with acute embolism (p < 0.001) and allowed for the identification of patients with acute embolism (p < 0.0001) when compared to controls [94]. Other studies have similarly found that LAA strain has a similar predictive power for ischaemic stroke compared to the CHADS-VASC2 score [95,96], and others' findings show that LAA strain can predict subclinical AF for patients with cryptogenic stroke [97]. GLS may also be able to predict post-stroke mortality [94].…”
Section: Ttementioning
confidence: 89%
“… 16 , 21 The Decryptoring score also used left atrial strain reservoir <25.3% and left atrial strain conduct <10.4%, which is in line with recent evidence showing that left atrial strain is a strong predictor at AF in patients with ESUS. 17 , 28 …”
Section: Discussionmentioning
confidence: 99%